Training of neurologists for the 21st century: cultural and professional skills - Nitrini, Ricardo (Arquivos de Neuro-Psiquiatria, 2022)
Background: Training of neurologists for the near future is a challenge due to the likely advances in neuroscientific methods, which will change much of our knowledge on diagnosis and treatment of neurological diseases. Objective: To comment on what may be more likely to be a constant in the very near future and to recommend how to prepare the neurologist for the 21st century. Methods: Through a critical review of recent articles on the teaching of Neurology, to present a personal view on the subject. Results: Diagnostic methods and therapeutic resources in Neurology will be greatly improved, but the central core of teaching young neurologists will continue to be the clinical/anatomical correlation. The neurologist must be prepared to be the primary physician in the care of patients with neurological disorders, although the roles of consultant and clinical neuroscientist must also be considered. In addition to technical knowledge, the neurologist must be prepared to discuss not only distressing issues related to the specialty, such as the risks of genetic diseases for family members of their patients, the inexorable progression of some diseases and the need for palliative care, but also problems not directly related to Neurology that cause anxiety and depression in the patient or that are the main reason for the initial consultation. Conclusion: neurology will be an even more important area of medicine and the neurologist must be well prepared to be the primary doctor to diagnose, treat and follow the patient with neurological disorders. In addition to technical knowledge, training in doctor-patient relations should be highlighted.
Keywords: Forecasting; Neurologists; Teaching; Mentoring; History, 21st Century; Humanism; Clinical-Anatomic Correlation